RESTRICTED MOVEMENT OF THE SPINE: AN ANALYSIS OF THE KNOWLEDGE OF NURSING PROFESSIONALS - Brigolini, Gabriela; Ciconet, Rosane Mortari (Cogitare Enfermagem, 2023)
Objective: To analyze nursing professionals’ knowledge about restricting spinal movement in trauma victims and describe their decision-making. Method: An exploratory, descriptive, qualitative-quantitative study. A semi-structured interview was conducted with 27 nursing professionals from hospital and pre-hospital emergency services in São Leopoldo, Brazil, in March 2022. The data was analyzed using descriptive statistics and content analysis. Results: 48% of the professionals knew the current recommendations; most worked in pre-hospital care. Cervicalgia/lumbago was the predominant indication. In the category “decision making and the transition of care”, a lack of standardization in in-hospital conduct was identified, emphasizing the importance of sequence in care and trust between professionals. Final considerations: It was found that in-hospital teams had little knowledge of the current evidence, a lack of standardization in procedures, and difficulties in the transition of care between services.